Materials selection analysis for vibration isolator pads - Zaman, Izzuddin; Subramaniyan, S Kanna; Sanusi, Shahmir Hayyan; Azmir, Nor Azali; Manshoor, Bukhari; Khalid, Amir (FAZ Publishing, 2020)
Isolator pads which also called as vibration pads are used in many applications to isolate vibration, extend machine life, reduce maintenance costs and reduce excessive wear. It is the process of isolating objects such as equipment from harmful vibration sources. In this study, two types of isolator pad materials; neoprene and sorbothone were analyzed in order to be used for stackable washing and dryer machine. In this case, the stackable washing and dryer machine together with the isolator pads were simplified into two degree of freedom system, where the first and the second natural frequencies for each material of isolator pad were determined by using matrix iteration method, in which later were validated by a modern tool such as Matlab. For neoprene material, the first natural frequency obtained was 44.2 rad/s and the second natural frequency is 107.7 rad/s. By contrast, sorbothone material shows slightly higher for both first and second natural frequencies compared to neoprene, which were 57.9 rad/s and 141.0 rad/s respectively. From this result, it shows that neoprene is suitable to be used as the coupling (spring) material since it has lower natural frequency value compared to sorbothone, besides the second natural frequency of sorbothone material is near to the forcing frequency 140 rad/s, thus could amplified the vibration due to resonance.